ANALISIS PEMASARAN KOPI BUBUK DI DESA LAKMARAS KECAMATAN LAMAKNEN SELATAN KABUPATEN BELU - Mali, Maria Ernita Lawa; Nubatonis, Agustinus; Metboki, Bernadina; Taena, Werenfridus (Agripreneur : Jurnal Pertanian Agribisnis, 2025)
This study aims to analyze marketing channels, marketing functions, marketing margins, and marketing profits of ground coffee in Lakmaras Village, Lamaknen Selatan District, Belu Regency. The method used in this study is a descriptive method with a quantitative and qualitative approach. Data were obtained through interviews, observations, and questionnaires with coffee farmers and business actors in the village.  The results of the study indicate that there are three main marketing channels for ground coffee in Lakmaras Village, namely (1) farmers–Bumdes–consumers, (2) Bumdes–contractors–consumers, and (3) Bumdes–contractors–retailers–consumers. Marketing functions include exchange, physical, and provision of facilities involving various marketing institutions in the ground coffee distribution chain. The highest marketing margin occurs in longer marketing channels, while the lowest marketing margin occurs in direct channels from farmers to consumers through Bumdes.  This study also found that marketing efficiency can be increased by shortening the distribution chain and strengthening the role of Bumdes in marketing ground coffee. With marketing optimization, it is expected that coffee farmers in Lakmaras Village can gain greater profits and increase the competitiveness of local ground coffee products.